Marital Agreements in Vietnam from 1858 until Now - Linh, NGUYỄN THỊ MỸ (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2021)
The institution of prenuptial agreement is a founder of contractual matrimonial property regime. The possibility of concluding a marriage contract contributes to ensuring the equal rights of the spouses, as they are free to agree on their pre-marital property. Recognizing the necessity of the contractual freedom in family law, the 2014 Act on Marriage and Family of Vietnam allows couples to choose between the statutory property regime and the agreed property regime. This article presents the history of the institution of marriage agreement in Vietnam, also with regard to the development of law in European countries.